Degradasi Musik Gambus Paser pada Sanggar Seni Sama Duwe di Desa Suatang Keteban Kabupaten Paser - Ashar, Saufitria; Gunawan, Asril; Putra, Bayu Arsiadhi (Jurnal Mebang: Kajian Budaya Musik dan Pendidikan Musik, 2024)
Gambus Paser music is one of the traditional art forms that is now experiencing degradation. The degradation of Gambus Paser's music occurs due to the influence of modernization, which affects the interest of the younger generation, who increasingly forget their traditional arts. In response to the degradation of Gambus Paser music, Sama Duwe Art Studio continues to make preservation efforts to maintain the values contained in Gambus Paser art. This preservation is not only carried out by the Sama Duwe Art Studio; the people of Suatang Keteban Village and the Paser Regency government must also help maintain and preserve the art of Gambus Paser music. This research uses qualitative methodology, including data collection, observation, and analysis techniques. Data collection has been done through literature studies, interviews, and documentation. The research theory used is the AGIL theory from Talcott Parson. The results showed that Paser Gambus music's degradation requires special attention from all parties. One form of community support and role can be observed from the role of the Sama Duwe Art Studio in preserving the art of Paser Gambus music in Suatang Keteban Village.